Historical Tropospheric and Stratospheric Ozone Radiative Forcing Using the CMIP6 Database. Issue 7 (6th April 2018) - Checa‐Garcia, Ramiro; Hegglin, Michaela I.; Kinnison, Douglas; Plummer, David A.; Shine, Keith P.
Abstract: We calculate ozone radiative forcing (RF) and stratospheric temperature adjustments for the period 1850–2014 using the newly available Coupled Model Intercomparison Project phase 6 (CMIP6) ozone data set. The CMIP6 total ozone RF (1850s to 2000s) is 0.28 ± 0.17 W m −2 (which is 80% higher than our CMIP5 estimation), and 0.30 ± 0.17 W m −2 out to the present day (2014). The total ozone RF grows rapidly until the 1970s, slows toward the 2000s, and shows a renewed growth thereafter. Since the 1990s the shortwave RF exceeds the longwave RF. Global stratospheric ozone RF is positive between 1930 and 1970 and then turns negative but remains positive in the Northern Hemisphere throughout. Derived stratospheric temperature changes show a localized cooling in the subtropical lower stratosphere due to tropospheric ozone increases and cooling in the upper stratosphere due to ozone depletion by more than 1 K already prior to the satellite era (1980) and by more than 2 K out to the present day (2014). Plain Language Summary: Radiative forcing is a key concept used in climate science to ascertain the strength of different agents, such as greenhouse gases or aerosols among others, in driving climate change. In this context, ozone is recognized as one of the main contributors to radiative forcing according to recent assessments of the Intergovernmental Panel on Climate Change. However, the relative uncertainty remains higher than for other greenhouse gases. This paper evaluates the ozone radiative forcing via calculations based on a newly created ozone data set for the Coupled Model Intercomparison Project (CMIP) phase 6, an initiative designed to better understand past, present, and future climate changes. In general, human activity has led to an increase in ozone concentrations in the lower atmosphere (the troposphere) and decreases in the upper atmosphere (the stratosphere); our paper investigates the effect of both these changes. Our results indicate that the CMIP ozone radiative forcing is 80% larger in the current phase 6 than a similar estimation based on data used in CMIP phase 5. We also present new insights into how ozone changes have led to stratospheric temperature changes, as well as the geographical distribution of ozone radiative forcing. Key Points: The 1850‐2010 ozone radiative forcing for the CMIP6 ozone database is 80% higher than for CMIP5 The long‐term stratospheric ozone radiative forcing in the Northern Hemisphere is positive despite recent ozone depletion Tropospheric and stratospheric ozone changes both lead to long‐term marked cooling patterns in the stratosphere